(untitled) (Bangladesh Veterinarian, 2010)
The role of omentum with or without antibiotic administration was evaluated in the healing of external wounds in goats. Nine goats aged 8-10 months and weighing 7-8 kg was randomly allocated into 3 groups as A: treated with omentum, B: omentum plus antibiotic and C: control. Experimental wounds about 2.5 cm long and 0.5 cm deep was produced on each side of the midline at the lumber region in each goat. Omentum 2 cm long and 0.4 cm wide obtained from an abattoir were lodged between the wound edges and apposed with nylon thread by simple interrupted suture. Complete healing was obtained on 11, 13 and 19 days in groups B, A and C, respectively. Rectal temperature, heart and respiratory rates showed no significant (p>0.05) variation during the healing period. On histopathological studies, highest degree of inflammation was observed in group C till day 15, but on day 5 in groups A and B. The rates of fibrosis of collagen fibre, epithelialization and neo-vascularization were most intensive in group B and then in group A and C till day 10. It is suggested that omentum along with antibiotic showed good healing in goats. DOI: 10.3329/bvet.v25i1.4612 Bangl. vet. 2008. Vol. 25, No. 1, 1-8